Effect of Arthrospira platensis extracts on glycation of BSA - Paramanya, Additiya; Ali, Ahmad (Acta Biologica Szegediensis, 2025)
Glycation, a non-enzymatic interaction between the carbonyl groups of sugars and the amino groups of macromolecules, leads to the formation of deleterious advanced glycation end-products (AGEs). Diseases such as neurodegenerative disorders, cardiovascular complications, and diabetes are characterized by the involvement of glycated products. This study investigated the antioxidant and antiglycation potential of a well-known cyanobacterium, Arthrospira platensis, through its extract. In an in vitro glycation system involving BSA and glucose, A. platensis PCC 7345 extracts (prepared in water- APA and buffer- APB) were incubated at 37 °C for 28 days. Antioxidant assays like ABTS, DPPH and NO Radical Scavenging Assay was performed. Quantification of glycation products was performed using spectroscopic methods, including browning, NBT assay, individual AGEs and fluorescent AGEs assessment. Both extracts demonstrated inhibitory effects on fructosamine content and AGEs, within the glycation system. Both APA and APB extracts from A. platensis effectively reduced browning reactions, with APA showing a slightly higher efficiency (51.67%) than APB (48.07%). Fructosamine assays revealed substantial reductions in ketoamine formation for both extracts, while the fluorometric determination of total AGEs indicated that APB exhibited superior antiglycating potency compared to APA, consistent with outcomes from fructosamine assays and supporting its effectiveness in attenuating glycation processes.